Official Language Minority Communities and Constitutional Amendments: A Study of Consociative Mechanisms in Canada - Tovar-Poitras, Mathieu (Université d'Ottawa / University of Ottawa, 2025)
English: This thesis explores to what extent official language minority communities participate in and exercise their autonomy during the process to amend the Canadian Constitution. The thesis is articulated by consociative federalism as theoretical framework. The concept is driven by a logic seeking the cohesion and the autonomy of various segments of a plural society through mechanisms operating in the interstices of the federal structure. The thesis first demonstrates that official language minority communities constitute a segment recognized in Canadian constitutional law. The analysis then delves on the application of consociational logic which highlights the segment's mechanisms to either take part or be autonomous in the midst of constitutional amendments. It sheds light on alternatives, notably through the political dimension of constitutional law. In all the thesis demonstrates the limited, but nuanced, space provided for the segment during the amending process. -- Français : Cette thèse débroussaille dans quelle mesure les communautés de langue officielle en situation minoritaire participent et exercent leur autonomie lors du processus de modification de la Constitution canadienne. La thèse s'articule avec le fédéralisme consociatif comme cadre théorique. Le concept est animé par une logique de recherche de la cohésion et de l'autonomie des différents segments d'une société plurielle à travers des mécanismes opérant dans les interstices de la structure fédérale. La thèse démontre d'abord que les communautés de langue officielle en situation minoritaire constituent un segment reconnu en droit constitutionnel canadien. L'analyse se penche ensuite sur l'application d'une logique consociative qui mettra en évidence les mécanismes à la disposition du segment pour soit prendre part, soit être autonome lors de modifications constitutionnelles. Elle mets en lumière des alternatives, dont à travers la dimension politique du droit constitutionnel. Somme toute, la thèse démontre l'espace limité, mais nuancé, accordé au segment pendant le processus de modification.
Keywords: Consociative federalism; Constitutional amendments; Official language minority communities; Amending process; Fédéralisme consociatif; Modifications constitutionnelles; Communautés de langue officielle en situation minoritaire; Processus d'amendement